Effect of Botulinum Toxin Injection on Asymmetric Lower Face with Chin Deviation - Dongwook Kim; Ju-Hyun Park; Vittorio Favero; James Mah; Young-Soo Jung; Seong Taek Kim (Toxins, 2020)
The purpose of this study was to compare the efficacy of botulinum toxin (BoNT) in masseter muscle reduction depending on the amount of chin deviation. Exploring distinctive effects of BoNT relative to the characteristics of facial asymmetry will aid in planning and predicting treatment outcomes. Sixteen adult volunteers were classified into two groups according to the degree of menton deviation observed in posteroanterior cephalograms. Eight had a menton deviation of 3 mm or more and the other eight had less than 3 mm. A total of 25 Units of BoNT was injected into the unilateral masseter muscle of the prominent side for each participant. Changes in the volume and bulkiest height of the lower face on each side were measured with a 3D laser scan at four time points: before and 4, 8, and 12 weeks after the injection. Two-way mixed ANOVA was employed for analyses. The volume and bulkiest height of the injected side decreased over time in both types of asymmetry, with significant differences at each time point. The reductions in the volume and bulkiest height were significantly greater in subjects without chin deviation. The reductions in the volume and bulkiest height of the lower face using BoNT are more effective for subjects without chin deviation.